Mode conversion of extraordinary waves in stratified plasmas with an external magnetic field perpendicular to the directions of inhomogeneity and wave propagation - Kim, Seulong; Kim, Kihong (Journal of the Korean Physical Society, 2021)
We study theoretically the mode conversion and the resonant absorption of high-frequency electromagnetic waves into longitudinal modes in magnetized and stratified plasmas in the case where the external magnetic field is perpendicular to both the directions of inhomogeneity and wave propagation. Mode conversion is shown to occur only when the waves are extraordinary waves. We develop an efficient method for calculating the mode conversion coefficient for arbitrary spatial configurations of the plasma density and the external magnetic field in a numerically exact manner using the invariant imbedding method. We calculate the mode conversion coefficient extensively as a function of the incident angle, the external magnetic field, and the plasma density in the incident region. We show that there is strong asymmetry under the sign change of the incident angle and the external magnetic field and find that the mode conversion coefficient is close to one in certain ranges of the parameter values. We discuss the implications of our results in plasma heating phenomena.
Keywords: Magnetized plasma; Mode conversion; Plasma heating; Resonant absorption; Upper hybrid resonance